EDUCATIONAL MANAGEMENT STRATEGIES IN OPHTHALMOLOGY SPECIALTY PROGRAMS (Proceedings of the International Conference on Education, 2021)
Medical specialty programs are aimed to train doctors in a specialization closely intertwined with a professional context. Progressively physicians experience more complexity and responsibility under the supervision of tutors and institutions approved for such purposes. For this program to be feasible to implement, institutions rely on their educational management strategies to plan, organize, lead, and control their process. This study aimed to assess these educational management strategies in specialty programs. The approach in this study was quantitative, with a descriptive and cross-sectional design. The sampling strategy was a convenience sample that consisted of the assessment of 22 programs of Ophthalmology. The assessment used an instrument of 13 items with a Likert scale of 5 levels ranging from 1, which stands for strongly disagree, to 5, which represents strongly agree. Results show a mean of 3.7 on the total scale, with a standard deviation of 1.4. The educational management strategy with the most favorable response was planning (mean = 3.9), and the least favorable response was found in leadership (mean = 3.5). These results indicate that educational institutions in health and medicine, particularly in Ophthalmology programs, have neglected to develop some management strategies, which must need to develop systematically. The universities must consider the establishment and adherence to good practices and policies, as these are part of establishing a quality educational program. A systematic analysis is needed to document and reflect the development, management, and institutional assessment of these strategies.
Keywords: educational innovation; higher education; medical education; educational management; ophthalmology